利用生物信息学、免疫组化分析肿瘤来源免疫球蛋白在非小细胞肺癌中的表达及临床意义 (Zhongguo Fei Ai Za Zhi, 2019)
BACKGROUND AND OBJECTIVE: It was believed that immunoglobulin G (IgG) was synthesized only by B cells. However, in recent years, researchers have found that a variety of cancer cells can also synthesize IgG (cancer-IgG) which promote the development of tumors. This study analyzed the expression and clinical significance of cancer-IgG in non-small cell lung cancer (NSCLC), and initially explored its mechanism. METHODS: The expression of IgG1 heavy chain gamma 1 (IGHG1) and cancer-IgG were detected by bioinformatics and immunohistochemistry in NSCLC; The gene set enrichment analysis (GSEA) method was used to explore the signaling pathways involved in IGHG1 regulation. RESULTS: The expression level of cancer-IgG in NSCLC was significantly higher than that in normal tissues. The high expression group had a poor prognosis and was associated with clinical stage (P=0.042), T stage (P=0.044) and metastasis (P=0.007). GSEA analysis showed that IGHG1 was associated with cell adhesion, cytokine interaction and chemokine signaling pathway. CONCLUSION: High expression of cancer-IgG in NSCLC is a poor prognosis factor, which may be related to the promotion of tumor invasion and metastasis.